The Position of Agreements and Arbitration Awards as A Legal Protection in Out-Of-Court Dispute Resolution - Adolf Theodore B. Simanjuntak; Zainal Arifin Hoesein (Yayasan Adra Karima Hubbi, 2024)
Background. In the era of globalization, the speed of economic activities fosters free markets and intense competition. Agreements play a crucial role in facilitating transactions, but disputes often arise due to differing interpretations or alleged breaches. Resolving these disputes efficiently and justly is essential to maintain trust and economic stability. Purpose. This research aims to determine the legal certainty and position of arbitration awards as a means of legal protection in out-of-court dispute resolution. Method. The study employs normative legal research with a focus on statutory and conceptual approaches. It analyzes laws and regulations related to arbitration, particularly Article 60 and Article 70 of the Arbitration Law. Results. Arbitration awards, as regulated in Article 60, are considered final, binding, and have permanent legal force. However, Article 70 allows parties to challenge arbitration awards by filing annulment requests, which undermines their finality. This duality creates ambiguity in the enforcement of arbitration awards. Conclusion. Although arbitration awards are designed to be final and binding, the provision for annulment in Article 70 diminishes their definitive status. Legal reforms are needed to enhance the finality of arbitration awards to strengthen their role in dispute resolution.